Evaluation of the Utility of von Willebrand Factor Propeptide in the Differential Diagnosis of von Willebrand Disease and Acquired von Willebrand Syndrome - Stufano, Francesca; Boscarino, Marco; Bucciarelli, Paolo; Baronciani, Luciano; Maino, Alberto; Cozzi, Giovanna; Peyvandi, Flora (Seminars in Thrombosis and Hemostasis, 2019)
An increased von Willebrand factor propeptide (VWFpp) to VWF antigen (VWF:Ag) ratio (VWFpp/VWF:Ag) indicates an enhanced clearance of VWF. This finding has been described in von Willebrand disease (VWD) and in acquired von Willebrand syndrome (AVWS). A distinction between these two diseases, one congenital and the other acquired, is primarily based on family and personal history of bleeding. However, if this information is scanty, the diagnosis might be challenging due to the lack of an effective diagnostic biomarker. In this cross-sectional study, we assessed the ability of VWFpp/VWF:Ag for the differential diagnosis between VWD and AVWS. VWFpp/VWF:Ag was measured in a group of 153 patients (125 with VWD and 28 with AVWS). Most patients with AVWS and VWD showed an increased VWFpp/VWF:Ag, although to variable degrees. A marked increase of VWFpp/VWF:Ag was mainly associated with the diagnosis of AVWS and VWD type 1 Vicenza. A receiver operating characteristic curve was used to identify the optimal cutoff of VWFpp/VWF:Ag for discrimination of patients with a modestly increased (most VWD cases) versus those with a markedly increased clearance (AVWS and VWD type 1 Vicenza), and this cutoff was identified at the value of 3.9 (sensitivity: 0.70, specificity: 0.97). The ROC curve sorting from a logistic model containing VWFpp/VWF:Ag, age, and sex had an area under the curve (AUC) of 0.88 (95% confidence interval: 0.80–0.95). A subsequent molecular evaluation discriminated VWD type 1 Vicenza from AVWS. In conclusion, VWFpp/VWF:Ag appears helpful to discriminate patients with a markedly increase VWF clearance (AVWS or VWD type 1 Vicenza) from those with a modestly increased clearance (most VWD patients).
Keywords: VWFpp; propeptide; von Willebrand disease; acquired von Willebrand syndrome